Adolescent Nutritional Status About Parental Feeding Practice And Macronutrient Intake - Pasaribu, Aisyah Pertiwi; Lestari, Anik; Priyatama, Aditya Nanda (Jurnal Kesehatan Manarang, 2024)
The nutritional status of adolescents remains a surpassing challenge for parents, society, and the healthcare sector. Adolescents' nutritional status can be affected by a variety of comprehensive factors, such as parental feeding practice and the daily intake of macro-nutrients. This study aimed to analyze the correlation between parental feeding practice and the daily intake of macro-nutrients among adolescents. This study is an analytical observational study with a cross-sectional design. The sample was collected from about 120 respondents using the stratified random sampling technique. Anthropometric measurements were collected using digital weight scales and microtoise. Parental feeding practice was assessed using the Adolescent Perceptions of Parents' Feeding Practice questionnaire, characteristic data and pocket money and the daily intake of macro-nutrients used the Semi Quantitative Food Frequency Questionnaire (SQ-FFQ). The data were collected and analyzed using the Chi-Square (p-value <0.05), followed by a multivariate logistic regression test (p-value <0.05). Around 51.7% of adolescents with malnutrition. The factors associated with the nutritional status of adolescents are parental feeding practice (p-value=0.017; OR=2.98), pocket money (p-value=0.118; OR=1.96), energy intake (p-value=0.246; OR=1.41), protein intake (p-value=0.087; OR=1.79), fat intake (0.975; OR=1.01), and carbohydrate intake (1.003; OR=0.41). Parental feeding practice, intake of energy and macronutrients, especially carbohydrates is related to the nutritional status of adolescents. There is no relationship between pocket money, protein intake and fat intake with nutritional status of adolescents. Based on multivariate analysis, it is reported that parental feeding practice and carbohydrates intake has a strong relationship with nutritional status of adolescents.